Analisis Dampak Kebijakan Pemulihan Ekonomi Nasional (Studi Kasus: Masa Pandemi Covid-19) - Fitrawaty, Fitrawaty; Maipita, Indra (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The Indonesian government through its national economic recovery policy (PEN) seeks to improve the economic conditions of the community with micro, small and medium enterprises (MSMEs) as a driving force for the economy. The purpose of this study was to analyze the effect of the number of MSME units, the number of workers and total non-oil exports on Indonesia's gross domestic product in the long term. Data comes from related agencies from 2000–2022. The data analysis method uses the classical assumption test stages including the autocorrelation test, multicollinearity test and heteroscedasticity test; then vector auto regression (VAR), vector error correction model (VECM), as well as significance and coefficient of determination tests. The results of the study explain that exports have no significant effect in the long term, while the number of MSMEs, labor, and GDP have a significant effect. The conclusion is that the PEN policy will be effective if all economic indicators increase simultaneously to generate economic growth